Development of a Thread-Based Interaction Model to Increase User Connection in Online Communities - Afrita, Juwika (Institut Manajemen Wiyata Indonesia, 2023)
This study applies a thread-based interaction model to enhance user connections within online communities, utilizing diffusion and analytical methods. The diffusion approach is employed to implement a thread structure that facilitates structured and focused conversations among users. These threads enable users to engage in discussions that are more organized and relevant to their interests. Furthermore, analytical methods are applied to map topics and connect related threads. Through the use of topic mapping algorithms, users can discover the most relevant threads aligned with their interests, thereby enhancing their engagement and participation within the community. During the experiment, the effectiveness of the interaction model is evaluated by measuring user connection and engagement levels. The research findings indicate that users are more likely to engage in deeper discussions and connect with other users through this approach. By combining the diffusion method for thread structuring and analytical methods for topic mapping, this study contributes to enhancing the ways users connect and interact within online communities.